Exploring the relationship between NOMAD quality and the performance of companies on AIM - Blessing, Gary (2015)
This study aims to explore the relationship between the Quality of Nominated Advisors (NOMADs) and the performance of companies on AIM. It begins by looking at the limitations of the junior market, specifically the underperformance of companies and poor investor returns. By gaining a comprehensive understanding of the governance structure on AIM, the research finds Nominated Advisors as the main influencers of standards. This dissertation conducts the first ever study that investigates the quality of NOMADs through the track record of its AIM clients. The findings show analysing NOMADs in this way will enable private investors to make better investment decisions. As the first paper to assess the performance of NOMADs, the researcher concludes by acknowledging some of the limitations of the study and proposes future research that can help enhance knowledge about the subject.